2006
DOI: 10.1134/s1063772906050106
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a filament due to magnetic-field variations in a complex active region

Abstract: Abstract-The complex active region NOAA 9672 is studied when it was near the central meridian, from October 21-26, 2001. At that time, there was an emergence of new magnetic flux, with the ongoing formation of a filament. The dynamics of the magnetic field are studied in order to search for their possible manifestations in the filament structure, using SOHO MDI magnetograms, SOHO EIT and TRACE filtergrams in the 171Å line, and Hα filtergrams available via the Internet. Our earlier conclusion that filaments for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Filament disturbance may be closely correlated with corresponding changes of the magnetic environment (Schmieder 1990). As for large-scale filaments in both quiet and active regions, some previous studies have shown that their disturbances can be greatly contributed to flux emergences and cancellations (Rust et al 1975;Wang et al 1996;Chen and Shibata 2000;Wang 2000, 2001;Moore et al 2001;Zhang et al 2001;Kim et al 2001;Moon et al 2004;Grigor'ev et al 2006;Archontis and Hood 2008). On the other hand, although the relationship between photospheric magnetic activities and small-scale filament eruptions have been studied only in a few cases (Hermans and Martin 1986;Sakajiri et al 2004;Zuccarello et al 2007), it appears that flux emergences and cancellations, like in the large-scale cases, play important roles in disturbing small filaments.…”
mentioning
confidence: 97%
“…Filament disturbance may be closely correlated with corresponding changes of the magnetic environment (Schmieder 1990). As for large-scale filaments in both quiet and active regions, some previous studies have shown that their disturbances can be greatly contributed to flux emergences and cancellations (Rust et al 1975;Wang et al 1996;Chen and Shibata 2000;Wang 2000, 2001;Moore et al 2001;Zhang et al 2001;Kim et al 2001;Moon et al 2004;Grigor'ev et al 2006;Archontis and Hood 2008). On the other hand, although the relationship between photospheric magnetic activities and small-scale filament eruptions have been studied only in a few cases (Hermans and Martin 1986;Sakajiri et al 2004;Zuccarello et al 2007), it appears that flux emergences and cancellations, like in the large-scale cases, play important roles in disturbing small filaments.…”
mentioning
confidence: 97%